Properties of polysaccharides and glutamine transaminase used in mozzarella cheese as texturizer and crosslinking agents. (January 2019) - Li, Hongjuan; Liu, Yan; Sun, Yanjun; Li, Hongbo; Yu, Jinghua
Abstract: Waxy rice starch, sodium carboxymethyl cellulose (CMC) and glutamine transaminase (TG) were used in mozzarella cheese as texturizers and crosslinking agents. The effects of waxy rice starch (1%), CMC (0.5%) and TG (0.5%) on the texture and rheological properties of mozzarella cheese were evaluated. Protein dissociation tests and the fluorescence probe method were used to evaluate the interactive forces in cheese. The results showed that cheeses with 0.5% CMC added had a smoother surface and lower degree of protein crosslinking. Waxy rice starch had a lower crosslinking effect on cheese. The detection of surface hydrophobicity revealed that CMC and TG promoted the hydrophobic interaction between molecules, whereas starch reduced the hydrophobic interaction. TG can significantly enhance the protein structure; however, it inhibits the meltability and stretchability of cheese. Highlights: CMC and TG were an effective texturizer and crosslinking agents in cheese. TG enhanced protein structure, while it inhibited the meltability and stretchability of cheese. Hydrogen bonding and hydrophobic forces were important in maintaining melting properties of cheese.